BCR, not TCR, repertoire diversity is associated with favorable COVID-19 prognosis - Paran, Faith Jessica; Oyama, Rieko; Khasawneh, Abdullah; Ai, Tomohiko; Ismanto, Hendra Saputra; Sherif, Aalaa Alrahman; Saputri, Dianita Susilo; Ono, Chikako; Saita, Mizue; Takei, Satomi; Horiuchi, Yuki; Yagi, Ken; et al. (Frontiers in Immunology, 2024)
The SARS-CoV-2 pandemic has had a widespread and severe impact on society, yet there have also been instances of remarkable recovery, even in critically ill patients. In this study, we used single-cell RNA sequencing to analyze the immune responses in recovered and deceased COVID-19 patients during moderate and critical stages. The study included three unvaccinated patients from each outcome category. Although expanded T cell receptor (TCR) clones were predominantly SARS-CoV-2-specific, they represented only a small fraction of the total repertoire in all patients. In contrast, while deceased patients exhibited monoclonal B cell receptor (BCR) expansions without COVID-19 specificity, survivors demonstrated diverse and specific BCR clones. These findings suggest that neither TCR diversity nor BCR monoclonal expansions are sufficient for viral clearance and subsequent recovery. Differential gene expression analysis revealed that protein biosynthetic processes were enriched in survivors, but that potentially damaging mitochondrial ATP metabolism was activated in the deceased.This study underscores that BCR repertoire diversity, but not TCR diversity, correlates with favorable outcomes in COVID-19.